Analisis Perilaku Nasabah Nonmuslim Dalam Memilih Produk Pembiayaan Murabahah Di Bank Syariah Indonesia KC. Jelutung Jambi - Hansen Rusliani; Putri Lestari; Nurrahma Sari Putri (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study aims to find out how to analyze the behavior of non-Muslim customers in choosing murabaha financing products, how to analyze the decision process of non-Muslim customers, and how cultural, social, personality and psychological factors can influence customer decisions in choosing murabaha financing products at Bank Syariah Indonesia KC. Jelutung Jambi. The method of this research is using descriptive qualitative method with primary and secondary data types. Data collection techniques in this study were observation, interviews and documentation techniques, while for data analysis the researchers used data reduction analysis, data presentation and verification. The theory used in this research is the theory put forward by Kotler & Ketler that consumer behavior is the science of how individuals, groups and organizations choose, buy and use and obtain goods, services, ideas or experiences to satisfy their wants and needs. . According to Kotlert's theory, consumer behavior is divided into four types, namely cultural, social, personality and psychological factors. In the customer decision process is divided into five steps, namely decision making, namely, recognition of needs, information search, evaluation of alternatives, buying decisions, and post-purchase evaluation. The results of the study explain that the behavior analysis of non-Muslim customers in choosing murabaha financing at Bank Syariah Indonesia KC. In Jelutung Jambi, there were three informants, namely the first informant who worked as a teacher because he was interested because of the salary slip through the bank, and chose gold installment financing because the bank could insure the gold installments, low interest rates, and cheap rates compared to pawn shops. The second informant is taking home installments because the interest rates are low compared to other banks and if you are late paying the installments you are not subject to a fine/sanction of 0.5% to 1% of the amount of the installments that the customer has to pay. The third informant is working as a teacher as well and taking education expenses for their children because the process is fast and the interest rate is low at 3.3%, while at commercial banks it is 8.93%. The fourth informant took gold installments because of the low interest rates. The fifth informant took motorbike installments because the interest rate was lower than leasing, which was 8%. From the several informants above, it can be concluded that cultural, social, personality and psychological factors can influence customer decisions in choosing murabaha financing products at Bank Syariah Indonesia KC. In Jelutung Jambi.